Molar Impactions: Etiology, Implications and Treatment Modalities with Presentation of an Unusual Case - Kaur, Manjot; Shefali, Singla (Journal of Orofacial Research, 2012)
Tooth development results from a complicated multistep interaction between the oral epithelium and the underlying mesenchymal tissue. Abnormal tissue interactions during tooth development may potentially result in ectopic tooth development and eruption. We report a case of unerupted second molar and impacted third molar and an attempt is made to review possible causes of noneruption of teeth and their treatment modalities. It is essential to diagnose and treat eruption disturbances as early as possible because treatment at a later stage is usually more complicated due to the tendency of malocclusion to increase with time and decrease the ability of remaining dentition to adjust.